Excitonic states and structural stability in two-dimensional hybrid organic-inorganic perovskites - Lekina, Yulia (2020)
Two-dimensional (2D) perovskites are a new class of functional materials that may find applications in various technologically important areas. Due to the better moisture and illumination stability, layered perovskites can be the next generation of materials for solar light-harvesting applications, as well as for light emitting diodes (LEDs). Besides, extended chemical engineering possibilities allow obtaining advanced perovskite materials with desirable functional properties, such as tunable band gap, strong exciton-phonon coupling, white light emission, spin-related effects, etc. A full understanding of the fundamental properties is essential for developing new 2D perovskite-based technologies. In this paper, recent reports on 2D perovskites are reviewed, including the synthesis methods of single crystals, nanosheets and films; the crystal and electronic structures; the excitonic states and interactions; the properties of the materials under low temperature and high pressure; and a brief discussion on the challenges in understanding the fundamental properties of the layered perovskites.